(untitled) (Revista Contexto & Educação, 2026)
The research deals with an analysis of the insertion of the History of Science (HC) in a collection of textbooks in the area of ​​Natural Sciences for the final years of Elementary School, approved in the PNLD 2020-2023. The methodology has a qualitative, exploratory, descriptive approach and for the analysis of the textbooks, Content Analysis was used. A total of 62 text insertions were found, distributed in four categories: (1) Scientist/Naturalist; (2) Scientific Activity; (3) Knowledge Production; and, (4) Contextualization of Science; and 64 images associated with these texts, having also established four categories of analysis: (1) Scientists/Naturalist; (2) Historical events and/or contextualizations of social, economic, environmental and/or model aspects; (3) Experiments with the presence of scientist(s); and, (4) Experiments. Finally, the contents associated with these insertions and their relationship with the BNCC were also investigated. The results also showed that there is room for improvement in some aspects. In general, the History of Science is presented as an ally to the study of Science, exposing concepts that do not harm, obstruct or mystify the critical and approximate understanding of science in relation to its reality.